BASIC QUESTIONING WITH PICTURE IN WRITING CLASS: IS IT EFFECTIVE? - Villia Rachmawati; Ana Maghfiroh; Restu Mufanti (Universitas Muhammadiyah Ponorogo, 2017)
This research was carried out to measure whether using basic questioning with picture is effective in teaching writing. The research design used in this reasearch was experimental research which consisted of two groups, experimental and control group. The sample of this research were X IPA1 as the experimental group which consisted of 32 students and X IPA2 as the control group which consisted of 30 students. The experimental group was taught by using basic questioning with picture while the control group was not taught by using basic questioning with picture, it was taught as usual or lecturing only. The instrument used to collect data was test. The test was writing test which was given in pre test and post test both two groups. The assessment of the result of writing test was focused on the five elements of writing (content, organization, vocabulary, language use, and mechanic). The technique to analyze the data used t-test formula.Two groups were compared. The result of statistical hypothesis on significance α=0.05 showed ttest (2.91) was higher than ttable (2.00). It means that, there was significant difference between the students who were taught by using basic questioning with picture and the students who were not taught by using basic questioning with picture in teaching writing. From the explanation above, it can be concluded that the use of basic questioning with picture is effective in teaching writing of the tenth year students of SMA Muhammadiyah 1 Ponorogo in Academic Year 2016/2017.